Conserved longitudinal alterations of anti-S-protein IgG subclasses in disease progression in initial ancestral Wuhan and vaccine breakthrough Delta infections - Goh, Yun Shan; Fong, Siew-Wai; Hor, Pei Xiang; Amrun, Siti Naqiah; Lee, Cheryl Yi-Pin; Young, Barnaby Edward; Chia, Po Ying; Tambyah, Paul A.; Kalimuddin, Shirin; Pada, Surinder; Tan, Seow-Yen; Sun, Louisa Jin; et al. (Frontiers in Microbiology, 2022)
COVID-19 has a wide disease spectrum ranging from asymptomatic to severe. While humoral immune responses are critical in preventing infection, the immune mechanisms leading to severe disease, and the identification of biomarkers of disease progression and/or resolution of the infection remains to be determined. We found an association between spike-specific IgM, IgA and IgG and disease severity in unvaccinated infected individuals. In addition to strong IgG1 and IgG3 response, patients with severe disease develop a robust IgG2 and IgG4 response. A comparison of the ratio of IgG1 and IgG3 to IgG2 and IgG4 showed that disease progression is associated with a smaller ratio in both the initial wave of WT and the vaccine breakthrough Delta infections. Time-course analysis revealed that smaller (IgG1 and IgG3)/(IgG2 and IgG4) ratio is associated with disease progression, while the reverse associates with clinical recovery. While each IgG subclass is associated with disease severity, the balance within the four IgG subclasses may affect disease outcome. Acute disease progression or infection resolution is associated with a specific immunological phenotype that is conserved in both the initial wave of WT and the vaccine breakthrough Delta infections.